2009
DOI: 10.1155/2009/159234
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Acoustic Features in Speakers with Cognitive Disorders and Speech Impairments

Abstract: This work presents the results in the analysis of the acoustic features (formants and the three suprasegmental features: tone, intensity and duration) of the vowel production in a group of 14 young speakers suffering different kinds of speech impairments due to physical and cognitive disorders. A corpus with unimpaired children's speech is used to determine the reference values for these features in speakers without any kind of speech impairment within the same domain of the impaired speakers; this is 57 isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Novak (1972) commented that the overlap of F1–F2 areas for different vowels may explain listener difficulties in distinguishing vowels in DS, although Moran (1986) found no difference between DS and controls. Similarly, Saz et al (2009) concluded from a study of Spanish speakers that errors in vowel identification were related to the confusability of vowel formant patterns, as well as to poor control over the energy in stressed versus unstressed vowels and excessive variability in vowel duration.…”
Section: Speech Sound Disorders (Table 2)mentioning
confidence: 99%
“…Novak (1972) commented that the overlap of F1–F2 areas for different vowels may explain listener difficulties in distinguishing vowels in DS, although Moran (1986) found no difference between DS and controls. Similarly, Saz et al (2009) concluded from a study of Spanish speakers that errors in vowel identification were related to the confusability of vowel formant patterns, as well as to poor control over the energy in stressed versus unstressed vowels and excessive variability in vowel duration.…”
Section: Speech Sound Disorders (Table 2)mentioning
confidence: 99%
“…Perceptual assessment of speech is done so as to get important information regarding articulation, resonance and speech intelligibility [1]. Perceptual assessment provides important information regarding misarticulation, resonance and speech intelligibility, In this present work ,it is observed that the speech disabled children produce misarticulation errors mainly due to weak motor movements and inappropriate closure of oral cavity uncoordinated articulator movements, breathing problems [6,7]. When speech is affected, all aspects of speech production may be affected including respiration, phonation, resonation, articulation, and prosody due to Rigidity of motor muscles , Velopharyngeal incompetency, Auditory processing, and Language impairments [2,10].…”
Section: Introductionmentioning
confidence: 71%
“…Devanāgarī alphabet for Marathi Consonants with IPA codes The isolated word speech data emphasized in the present work is described below. It indicates case studies of different types of Articulation errors with respect to both place of articulation and manner of articulation [6,7]. Table 3 lists the place of articulation and manner of articulation for marathi words.…”
Section: Suprasegmental Factors Concerned With Marathi Languagementioning
confidence: 99%
“…The results of the F0 reduction in the SIG are similar with [37], where F0 tend to be lower for impaired speech. However, some studies have reported that there is no significant difference in F0 decrement in impaired speech [21]. This is because individuals with speech impairment can still control some prosodic features in their speech, even though they lose intelligibility in the vowel production [21] [10].…”
Section: Fig 2: Comparison Of Wer Between Sig and Cgmentioning
confidence: 99%